Determination and persistence of methiocarb in artichokes - Cabras, P.; Angioni, A.; Melis, M.; Spanedda, L.; Minelli, E. V. [UNESP] (My University, 1996)
A simple and rapid method for the determination of methiocarb in artichokes by high-performance liquid chromatography with UV detection is described. No derivatization is needed and the limit of determination (0.01 ppm) is analogous to that of fluorometric detection. The results of trials carried out with granular and liquid formulations of this active ingredient are also reported. Immediately after treatment with the liquid formulation methiocarb residues averaged 1.47 ppm, while after treatment with the granular formulation residues were considered fortuitous. The decay rate of methiocarb residues in artichokes shows that the decrease and eventual disappearance of this active ingredient can chiefly be ascribed to the dilution effect due to head growth.
Keywords: Artichoke; Determination; Methiocarb; Persistence